The latest trends in translator training in German higher education institutions (Educational Dimension, 2021)
The article focuses on identifying current trends in translator education in German higher education institutions. The focus is on the educational content of future interpreters. The following trends in the organization and content of translator study have recently become particularly important in German universities: compulsory practice abroad, study of specialized information technologies, offering dual specialization, implementation of translation programs with a narrow specialization, interdisciplinary orientation in the study of special courses, formation of soft skills. It is suggested that these trends should be taken into account in the educational process of domestic higher education institutions.